10x+3=6x-5

Simple and best practice solution for 10x+3=6x-5 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 10x+3=6x-5 equation:



10x+3=6x-5
We move all terms to the left:
10x+3-(6x-5)=0
We get rid of parentheses
10x-6x+5+3=0
We add all the numbers together, and all the variables
4x+8=0
We move all terms containing x to the left, all other terms to the right
4x=-8
x=-8/4
x=-2

See similar equations:

| 3(k-2)=9k-4k+10 | | 4=5(x-9)-8x | | w+56=9w | | 7(g−19)=−14 | | 2z+4(z+5)=1/2z+5 | | -8y+56=-8(y-7) | | 5/25=9/x | | 1+12z=29 | | -4w-85=5+5w | | 11-6r=2r+3 | | -5h-8=-5+8 | | -6(-4u+8)-5u=5(u+7)-9 | | 21-7d=1-2d | | 6+z/3=1 | | 2x+22=5(x+2) | | -24z-15=-27 | | 5y+14=7y | | 3(w+3)-7w=-15 | | 9x+3-(x-1)=6(x+10) | | 18-6.3z=49.5 | | 9x+3-x-1=6(x+10) | | x+x.05=252 | | 10g-2(8+5g)=16 | | 9m+1m=3m+13 | | 20.1/5+d=23 | | 5x-6=(x-1 | | x²-6x+9=-9x+19 | | x−5=−122.−4x=28 | | 8x²-56x=0 | | 4/9x+20=-5(4x+2)-30 | | 56x=8² | | 271/2-5x=31/2 |

Equations solver categories